First results of PACTE group’s experimental research on translation competence acquisition: the acquisition of declarative knowledge of translation - Research Group, PACTE (MonTi Monografías de Traducción e Interpretación, 2015)
This paper presents the first results of empirical-experimental research into the Acquisition of Translation Competence (ATC): the acquisition of declarative knowledge about translation. This study is based on our previous research about Translation Competence (TC). Some of the data collection instruments have, however, been adapted for current use. Details of our research design include type of study, universe and sample population, study variables, data collection instruments, and data analysis processes. The dependent variables were knowledge of translation; translation project; identification and solution of translation problems; decision-making; efficacy of the translation process; and use of instrumental resources. The results of the first variable analysed (“Knowledge of Translation”) will be presented. A questionnaire with 27 items was used to obtain data on translator trainees’ knowledge of translation: their concept of translation and TC; translation units; types of translation problems; the different phases involved in the translation process; methods required; procedures used (strategies and techniques); and the role of the translation brief and the target reader. Indicators of this variable were ‘dynamic index’ and ‘coefficient of coherence’. We understand a ‘dynamic’ concept of translation to be textual, interpretative, communicative and functional; as opposed to a ‘static’ concept that may be defined as linguistic and literal. The dynamic index allows us to see whether a subject’s implicit knowledge about how translation works is more dynamic or more static, whereas the coherence coefficient allows us to see whether the subject’s vision of different aspects of translation is coherent.